Peran Pembelajaran Sejarah Dalam Mempersiapkan Generasi Emas Melalui Penanaman Nilai Karakter Nasionalime - Riki Andi Saputro (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The golden generation is the generation that is able to answer the challenges of the 21st century. So to give the golden generation in Indonesia the need for support from education. The purpose of education is to create someone of quality and character. Historical education is essentially the cultivation of a sense of time without which one would lose temporal orentation. The relationship between historical education and character education is the purpose of learning history and character building. Character or identity. Purpose of Study: To find out how the role of historical learning in preparing the golden generation through the cultivation of the character value of nationalism. Method: A method of literature that is descriptive of analytical. Results of study: The rise of the golden generation in the golden age, Historical learning and character education, The Value of Nationalism character in historical learning. Conclusion: The golden generation aspired by the Indonesian nation is a character, critical thinking, creative, innovative, communicative, collaborative, and competitive. Related to the development of the global era, education experts agree that the 21st century as the Conceptual Era.